2007
DOI: 10.1021/la702157r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Photocatalytic Activities, and Dye-Sensitized Solar-Cell Performance of Submicron-Scale TiO2 Hollow Spheres

Abstract: We prepared submicron-scale spherical hollow particles of anatase TiO2 by using a polystyrene-bead template. The obtained particles were very uniform in size, with a diameter of 490 nm and a shell thickness of 30 nm. The Brunauer-Emmett-Teller surface area measurements revealed a large value of 70 m2/g. The photocatalytic property was investigated by the complete decomposition of gaseous isopropyl alcohol under UV irradiation. It was indicated that the activity of the hollow spheres was 1.8 times higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
161
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(163 citation statements)
references
References 26 publications
1
161
0
1
Order By: Relevance
“…For example, Li et al [21] found that the photocatalytic activity of the ''semi-hollow'' core-shell structured TiO2 increased compared to the ''fully-hollow'' structured TiO2, suggesting that the multiple reflections of the incident light within the interior cavity of the hollow structure resulted in an enhanced light harvesting efficiency. This claim of enhancement of the photocatalytic activity by multiple reflections was echoed by others for TiO2 hollow structures [22][23][24][25], and also claimed later for other hollow materials such as ZnO [26,27], NiO [28], SnO [29], CdS [30], Fe2O3 [31] and carbon nitride [32]. However, as generally known, the multiple reflections within the interior cavity should occur only when the cavity diameter is much larger than the wavelength of the incident light [33,34].…”
Section: Introductionmentioning
confidence: 84%
“…For example, Li et al [21] found that the photocatalytic activity of the ''semi-hollow'' core-shell structured TiO2 increased compared to the ''fully-hollow'' structured TiO2, suggesting that the multiple reflections of the incident light within the interior cavity of the hollow structure resulted in an enhanced light harvesting efficiency. This claim of enhancement of the photocatalytic activity by multiple reflections was echoed by others for TiO2 hollow structures [22][23][24][25], and also claimed later for other hollow materials such as ZnO [26,27], NiO [28], SnO [29], CdS [30], Fe2O3 [31] and carbon nitride [32]. However, as generally known, the multiple reflections within the interior cavity should occur only when the cavity diameter is much larger than the wavelength of the incident light [33,34].…”
Section: Introductionmentioning
confidence: 84%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In addition, TiO 2 nanoparticles (NPs) are also used in the preparation of nanocomposites in order to enhance the optical, mechanical, electrical, and thermal properties of polymeric materials. [13][14][15][16][17][18] Despite their inherent excellent properties, TiO 2 NPs have several drawbacks such as agglomeration and poor interaction with organic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thin-film solar cells such as dye-sensitized solar cells and organic photovoltaic have been studied extensively by our group [1][2][3][4][5][6][7][8][9] because they can be assembled with low-cost materials and manufactured with cost-effective methods, which are considered to be very promising renewable energy technologies.…”
Section: Introductionmentioning
confidence: 99%